Intra and Interspecific Relation of Tree Species Aspects of Seed Biometry, Phenology, Seed Dispersion, and Germination - Chowdhury, Mohd Imran Hossain; Rakib, Mehedi Hasan; Das, Chinmoy (Journal of Agriculture Sustainability and Environment, 2023)
Bangladesh, with its dense population and diverse ecological landscape, embodies a unique environmental tapestry. This study explores the intricate interplay between tree phenology, seed dispersal seed germination, and biometric characteristics within the context of Bangladesh's rich biodiversity. Through field research conducted from 2020 to 2023 in the Chittagong division, we investigated species such as Artocarpus chama, Avicennia officinalis, Terminalia arjuna, Terminalia bellirica, and Terminalia chebula. The findings reveal significant variations in seed morphology, phenology, germination, and ecological roles among these species. Furthermore, through dendrogram analysis and principal component analysis (PCA), we elucidate the underlying patterns and relationships governing biometric variability. These insights provide valuable contributions to our understanding of ecological processes and inform conservation strategies aimed at preserving Bangladesh's forest tree biodiversity.